A longitudinal assessment of the serological response to Theileria parva and other tick-borne parasites from birth to one year in a cohort of indigenous calves in western Kenya - Kiara, Henry K.; Jennings, A.; Bronsvoort, B.M. de C.; Hande, I.G.; Mwangi, S.T.; Mbole-Kariuki, Mary N.; Wyk, Ilana Conradie van; Poole, Elizabeth J.; Hanotte, Olivier H.; Coetzer, Jacobus A.W.; Woolhouse, Mark E.J.; Toye, Philip G. (Cambridge University Press, 2014)
Tick-borne diseases are a major impediment to improved productivity of livestock in sub-Saharan Africa. Improved control of these diseases would be assisted by detailed epidemiological data. Here we used longitudinal, serological data to determine the patterns of exposure to Theileria parva, Theileria mutans, Babesia bigemina and Anaplasma marginale from 548 indigenous calves in western Kenya. The percentage of calves seropositive for the first three parasites declined from initial high levels due to maternal antibody until week 16, after which the percentage increased until the end of the study. In contrast, the percentage of calves seropositive for T. mutans increased from week 6 and reached a maximal level at week 16. Overall 423 (77%) calves seroconverted to T. parva, 451 (82%) toT. mutans, 195 (36%) to B. bigemina and 275 (50%) to A. marginale. Theileria parva antibody levels were sustained following infection, in contrast to those of the other three haemoparasites. Three times as many calves seroconverted to T. mutans before seroconverting to T. parva. No T. parva antibody response was detected in 25 calves that died of T. parva infection, suggesting that most deaths due to T. parva are the result of acute disease from primary exposure.